In Vivo MRI Tracking of Mesenchymal Stromal Cells Labeled with Ultrasmall Paramagnetic Iron Oxide Particles after Intramyocardial Transplantation in Patients with Chronic Ischemic Heart Disease - Anders Bruun Mathiasen; Abbas Ali Qayyum; Erik Jørgensen; Steffen Helqvist; Annette Ekblond; Michael Ng; Kishore Bhakoo; Jens Kastrup (Stem Cells International)
Background. While regenerative stem cell therapy for ischemic heart disease has moved into phase 3 studies, little is still known about retention and migration of cell posttransplantation. In human studies, the ability to track transplanted cells has been limited to labeling with radioisotopes and tracking using nuclear imaging. This method is limited by low resolution and short half-lives of available radioisotopes. Longitudinal tracking using magnetic resonance imaging (MRI) of myocardial injected cells labeled with iron oxide nanoparticles has shown promising results in numerous preclinical studies but has yet to be evaluated in human studies. We aimed to evaluate MRI tracking of mesenchymal stromal cells (MSCs) labeled with ultrasmall paramagnetic iron oxide (USPIO) nanoparticles after intramyocardial transplantation in patients with ischemic heart disease (IHD). Methods. Five no-option patients with chronic symptomatic IHD underwent NOGA-guided intramyocardial transplantation of USPIO-labeled MSCs. Serial MRI scans were performed to track labeled cells both visually and using semiautomated T2∗ relaxation time analysis. For safety, we followed symptoms, quality of life, and myocardial function for 6 months. Results. USPIO-labeled MSCs were tracked for up to 14 days after transplantation at injection sites both visually and using semiautomated regional T2∗ relaxation time analysis. Labeling of MSCs did not impair long-term safety of treatment. Conclusion. This was a first-in-man clinical experience aimed at evaluating the utility of MRI tracking of USPIO-labeled bone marrow-derived autologous MSCs after intramyocardial injection in patients with chronic IHD. The treatment was safe, and cells were detectable at injection sites up to 14 days after transplantation. Further studies are needed to clarify if MSCs migrate out of the injection area into other areas of the myocardium or if injected cells are washed out into the peripheral circulation. The trial is registered with ClinicalTrials.gov NCT03651791.